Bráquetes autoligados passivos: desenho e prescrição - Tocolini, Daniel Gheur (2018)
In Orthodontics, it is constant the search for bracket designs that allow more physiological movements with prescriptions that adapt to the biomechanical characteristics and promote greater comfort for the users of fixed orthodontic appliances. The objectives of this thesis were: 1. To develop new designs of passive self-ligating brackets (two industrial design patent registers and one utility model patent); 2. Compare the slot and torque angle measurements of different metallic passive self-ligating brackets (Manuscript 1); 3. Describe step-by-step the TCONTROL Philosophy, developed for orthodontic planning and treatment, with a new two-dimensional orthodontic prescription for passive self-ligating devices to treat different types of malocclusions (Manuscript 2). For the study of the manuscript 1, 5 different brands of passive self-ligating metal brackets (n=10) were selected: Tellus EX, Tellus EX New, Damon Q, Easy Clip and ID-Logical. Images of bracket slots were obtained using the digital profile projector. Measurements of the slots were carried out in the cervico-occlusal (height) and in the buccal-lingual (depth) directions. Also, measurements of the base of the brackets (torque angle) were evaluated. The difference between the measurement obtained and the measurement provided by the manufacturer was calculated as a percentage. Data were submitted to descriptive statistical analysis. It could be observed that most of the evaluated brackets showed a variation of the torque angle and the slot measurements greater than that reported by the manufacturer (Easy Clip, Damon Q and Tellus EX), except for two brackets (Tellus EX-New and ID-Al) that presented a variation considered normal, within the values accepted by ISO. In manuscript 2, a new two-dimensional orthodontic prescription for the T-CONTROL Philosophy was described, which was applied in the treatment of the malocclusion of a patient with Class III skeletal, Angle Class III, open bite, facial asymmetry, mandibular deviation, occlusal plane and smile inversion. Based on the studies presented in this thesis, it can be concluded that the metallic passive self-ligating brackets evaluated presented differences in relation to the parameters provided by the manufacturer, for both the torque angulation and the slot measurements. This may have consequences on biomechanics and orthodontic treatment outcomes. The new two-dimensional prescription and the T-CONTROL Philosophy presented good results in the correction of Class III malocclusion exposed in the clinical case.